Description of the male and the southernmost record of Mesoveloidea williamsi Hungerford, 1929 (Hemiptera: Heteroptera: Mesoveliidae) - Moreira, Felipe Ferraz Figueiredo; Ribeiro, José Ricardo Inacio; Nessimian, Jorge Luiz (Zootaxa, 2006)
The male of Mesoveloidea williamsi Hungerford, 1929 and its genitalia are described and illustrated for the first time. The first record of the species from Rio de Janeiro State, Brazil, the southernmost record of the species, is presented.